Estimating dynamic cattle population on palm oil plantation area in South Kalimantan Province) - Adinata, Yudi; Pamungkas, Dicky; Krishna, Noor Hudhia; Aryogi, Aryogi (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2014)
Integration between beef cattle and palm oil plantation (animal plantation integration) should be supportedand developed. This study was carried out to estimate the dynamic cattle population managed by PT KAL.Estimating dynamic cattle population was counted by simulation base on population data, animal physiologicalstatus, and forage carrying capacity under palm oil plantation. The carrying capacity of available space is 2.066 ±199 animal unit (AU) and naturally would be reached in 2029-2030. Optimal capacity would be reached faster byintroducing new cattle in the population.Key words: integration, beef cattle, palm oil, dynamic cattle population